CONCEPTUAL SYSTEM-DYNAMIC MODEL OF SEAFOOD LOGISTICS - Ivanov, Serhii (Collection of scientific papers «ΛΌГOΣ», 2024)
Introduction. Fish as well as various seafood products, as one of the most useful sources of protein, are an essential component of the diet of many people in the world and in Ukraine in particular. However, the actual extraction and consumption of aquatic biological resources in recent years does not meet real needs. Due to objective circumstances, not only in wartime, but also in peacetime, Ukraine is unable to catch or grow many types of fish and seafood on its own, therefore more than 85% of all fish products consumed by Ukrainians are imported, and by volume ranks first among all food products imported into Ukraine.